Tsc1 Haploinsufficiency Leads to Pax2 Dysregulation in the Developing Murine Cerebellum - Serra, Ines; Stravs, Ana; Osório, Catarina; Oyaga, Maria Roa; Schonewille, Martijn; Tudorache, Christian; Badura, Aleksandra (Frontiers in Molecular Neuroscience, 2022)
Tuberous sclerosis complex 1 (TSC1) is a tumour suppressor that promotes the inhibition of mechanistic target of rapamycin (mTOR) pathway, and mutations in TSC1 lead to a rare complex disorder of the same name. Despite phenotype heterogeneity, up to 50% of TSC patients present with autism spectrum disorder (ASD). Consequently, TSC models are often used to probe molecular and behavioural mechanisms of ASD development. Amongst the different brain areas proposed to play a role in the development of ASD, the cerebellum is commonly reported to be altered, and cerebellar-specific deletion of Tsc1 in mice is sufficient to induce ASD-like phenotypes. However, despite these functional changes, whether Tsc1 haploinsufficiency affects cerebellar development is still largely unknown. Given that the mTOR pathway is a master regulator of cell replication and migration, we hypothesised that dysregulation of this pathway would also disrupt the development of cell populations during critical periods of cerebellar development. Here, we used a mouse model of TSC to investigate gene and protein expression during embryonic and early postnatal periods of cerebellar development. We found that, at E18 and P7, mRNA levels of the cerebellar inhibitory interneuron marker Pax2 were dysregulated. This dysregulation was accompanied by changes in the expression of mTOR pathway-related genes and downstream phosphorylation of S6. Differential gene correlation analysis revealed dynamic changes in correlated gene pairs across development, with an overall loss of correlation between mTOR- and cerebellar-related genes in Tsc1 mutants compared to controls. We corroborated the genetic findings by characterising the mTOR pathway and cerebellar development on protein and cellular levels with Western blot and immunohistochemistry. We found that Pax2-expressing cells were largely unchanged at E18 and P1, while at P7, their number was increased and maturation into parvalbumin-expressing cells delayed. Our findings indicate that, in mice, Tsc1 haploinsufficiency leads to altered cerebellar development and that cerebellar interneuron precursors are particularly susceptible to mTOR pathway dysregulation.